Experimental Study on the DRTA Strategy: Improving Arabic Reading Activeness in Madrasah Tsanawiyah Batu - Miranda, Ayu; Syuhadak, Syuhadak; Agil, Idrus Muchsin Bin; Zamziba, Muhammad Nur Farhan (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2025)
Arabic texts often have complex structures and vocabulary, requiring effective strategies for student engagement. The Directed Reading Thinking Activity (DRTA) strategy encourages students to make predictions, check their understanding, and evaluate texts actively. This study aims to examine the effectiveness of DRTA in enhancing student engagement in reading skill learning. Using a quasi-experimental approach, it analyzes students' participation and comprehension before and after DRTA implementation. The results show that active involvement in learning is key to success. DRTA helps students comprehend materials more easily and develop critical thinking skills. The experimental class using DRTA showed significant improvement in test scores, from 34.00 to 70.00, while the non-experimental class showed little change. This emphasizes the importance of active, interactive learning in improving outcomes. The study suggests that DRTA is effective in enhancing Arabic reading skills, critical thinking, and problem-solving abilities.